A Proposal for Simplifying the Method of Evaluation of Uncertainties in Measurement Results - Kušnerová M.; Valíček J.; Harničárová M.; Hryniewicz T.; Rokosz K.; Palková Z.; Václavík V.; Řepka M.; Bendová M. (Measurement Science Review, 2013)
The paper deals with the innovative ways of nonstandard, simplifying applications of the valid method for evaluating uncertainties in measurement results and with the definition of conditions of their usability. The evaluation of a substitute criterion for measurement accuracy by means of a relative difference between the measurand and its reference value is proposed. This nonstandard relative uncertainty is comparable with the overall relative standard uncertainty in the measurement result, and thus the evaluation of it enables other simplifications in the calculations of measurement result uncertainties. The use of the simplified evaluation of measurement results is illustrated in two experiments in measurement of the coefficient of thermal conductivity of an insulating material newly developed for the needs of building practice, namely measurement using commercial instruments, and measurement using a newly developed original measuring instrument.